2016
DOI: 10.1021/acs.iecr.6b01359
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Hg(II) Removal Efficiency from Real Wastewater by Novel Thymine-Grafted Reduced Graphene Oxide Complexes

Abstract: In this study, the reduced graphene oxide was modified by grafting thymine on its surface. The resultant reduced graphene oxide-thymine composite (rGO-Thy) exhibits a higher Hg(II) adsorption capacity and selectivity compared with rGO as the functional group of thymine shows a strong affinity toward Hg(II) and form thymine-Hg(II)-thymine complex. The relative selectivity coefficients of rGO-Thy for Hg(II)/Pb(II), Hg (II)/Ni(II), Hg (II)/Co(II), Hg (II)/Cu(II) and Hg(II)/Cd(II) are 21.72, 7.08, 5.37, 4.37 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…The decrease in the removal of mercury above pH 5.5 is related to the formation of insoluble Hg(OH) 2 and it keeps constant for pH higher than 5. This may be attributed to the competitive adsorption from OH-ions by the formation of the hydrogen bonding leading to a decrease in the number of available adsorption sites [10].…”
Section: Effect Of Ph On Hg(ii) Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the removal of mercury above pH 5.5 is related to the formation of insoluble Hg(OH) 2 and it keeps constant for pH higher than 5. This may be attributed to the competitive adsorption from OH-ions by the formation of the hydrogen bonding leading to a decrease in the number of available adsorption sites [10].…”
Section: Effect Of Ph On Hg(ii) Adsorptionmentioning
confidence: 99%
“…Most of mercury in wastewater exists in the form of mercury ions. Thus, to protect ecosystems, the discharge of Hg(II) is under strict regulatory limits, and the permissible concentration limit of mercury in drinking water is 2 ppb according to the United States Environmental Protection Agency (EPA) [10]. Until now, various techniques have been utilized to extract/reduce Hg(II) ions from aquatic solutions such as precipitation, adsorption, membrane process, chemical coagulation, and ion exchange [1,11].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…In another approach of surface functionalization of rGO, grafting of thymine on rGO was carried out, which increased the selectivity of rGO for the adsorption of Hg(II) ions as compared to pristine rGO [111]. This enhanced affinity of thymine-grafted rGO for Hg(II) ions is attributed to the formation of an rGO-thymine-Hg(II) complex, which increased the adsorption capacity of Hg(II) ions to 128 mg g -1 from 60 mg g -1 on pristine rGO.…”
Section: Reduced Graphene Oxidementioning
confidence: 99%
“…Several research groups have reported the adsorption properties of GO for heavy metal ions on its surface via surface complexation, p-p interaction or by electrostatic interactions. 24,[26][27][28] Therefore, GO seems to be an ideal adsorbent in the extraction of metal ions. However, direct use of GO in aqueous media is challenging because of strong van der Waals forces and p-p interaction, they tend to agglomerates and signicantly limits its surface area and adsorption activity.…”
Section: Introductionmentioning
confidence: 99%